Improving Pharmacy Students’ Clinical Knowledge on Providing Care for Patients Belonging to the LGBTQ+ Community - Tyler C. Melton; William T. Johnson; Brittany Tipton; Kelsea G. Aragon; Calvin C. Daniels; Chelsea Phillips Renfro (Pharmacy, 2022)
A 12-question survey instrument was developed, pilot-tested, and administered to 191 pharmacy students in their first professional year after engaging in a learning activity focusing on topics across five categories with clinical relevance to providing care to the LGBTQ+ community. A paired student t-test was performed on survey tool pre-test and post-test survey responses, with p < 0.05 considered significant. A total of 183 usable pre-test and post-test survey responses were received. Statistically significant differences between the pre-test and post-test correct responses were observed for scenarios involving proper pronoun use, hormone therapy (HT) counseling, immunization best practices, and communication hesitancy. The greatest knowledge change was reported in the categories of immunization best practices (48.9%), HT counseling (33.6%), and pronoun use (22.8%). Active learning assignments are effective teaching strategies to promote clinical knowledge in providing inclusive and culturally competent care to LGBTQ+ patients. Clinical topic areas including proper pronoun use, HT counseling, immunization best practices, privacy, risk awareness, and communication hesitancy are effective curricula additions for pharmacy colleges to advance inclusive curricula concerning providing care to the LGBTQ+ community.